Due Diligence in Financial Aspects for Remedies Postpartum Care Center - Saptiangga Sartono; Rhian Indradewa; Unggul Kustiawan; Rian Adi Pamungkas (Return : Study of Management, Economic and Bussines, 2025)
This study evaluates the financial feasibility of the Remedies Postpartum Care Center, which aims to provide holistic health services for postpartum mothers during the critical period of 0-14 days after delivery. The purpose of this study is to assess the feasibility of investment by conducting a financial due diligence analysis, including revenue projections, Return on Investment (ROI), Net Present Value (NPV), and Internal Rate of Return (IRR) calculations. The results showed that the average ROI reached 16.93%, with a positive NPV and a payback period of four years. In addition, the IRR was recorded at 44% in the fifth year, indicating that the project was feasible. The findings also showed that Remedies had no short- or long-term debt, with a current ratio of 2.64 times. The Remedies Postpartum Care Center has good prospects based on the financial analysis conducted. With a solid risk management strategy and significant revenue projections, the project is feasible for implementation. This research provides guidance for investors and entrepreneurs in assessing the feasibility of healthcare projects. The results can be used as a reference for policy development to support postpartum care centers in Indonesia.